Structural modeling identifies Plasmodium vivax 4-diphosphocytidyl-2C-methyl-d-erythritol kinase (IspE) as a plausible new antimalarial drug target. Issue 4 (August 2018) - Kadian, Kavita; Vijay, Sonam; Gupta, Yash; Rawal, Ritu; Singh, Jagbir; Anvikar, Anup; Pande, Veena; Sharma, Arun
Abstract: Malaria parasites utilize Methylerythritol phosphate (MEP) pathway for synthesis of isoprenoid precursors which are essential for maturation and survival of parasites during erythrocytic and gametocytic stages. The absence of MEP pathway in the human host establishes MEP pathway enzymes as a repertoire of essential drug targets. The fourth enzyme, 4-diphosphocytidyl-2C-methyl-d -erythritol kinase (IspE) has been proved essential in pathogenic bacteria, however; it has not yet been studied in any Plasmodium species. This study was undertaken to investigate genetic polymorphism and concomitant structural implications of the Plasmodium vivax IspE ( Pv IspE) by employing sequencing, modeling and bioinformatics approach. We report that Pv IspE gene displayed six non-synonymous mutations which were restricted to non-conserved regions within the gene from seven topographically distinct malaria-endemic regions of India. Phylogenetic studies reflected that Pv IspE occupies unique status within Plasmodia genus and reflects that Plasmodium vivax IspE gene has a distant and non-conserved relation with human ortholog Mevalonate Kinase (MAVK). Structural modeling analysis revealed that all Pv IspE Indian isolates have critically conserved canonical galacto-homoserine-mevalonate-phosphomevalonate kinase (GHMP) domain within the active site lying in a deep cleft sandwiched between ATP and CDPME-binding domains. The active core region was highly conserved among all clinical isolates, may be due to >60% β-pleated rigid architecture. The mapped structural analysis revealed the critically conserved active site of Pv IspE, both sequence, and spacially among all Indian isolates; showing no significant changes in the active site. Our study strengthens the candidature of Plasmodium vivax IspE enzyme as a future target for novel antimalarials. Graphical abstract: Unlabelled Image Highlights: Genetic characterization of IspE gene from Indian P. vivax clinical isolates. Four distinct genotypes of IspE identified from all over India for the first time. Mutations were scattered only in non conserved regions. Active site was highly conserved among all the isolate models. This study confirms Pv IspE as a plausible antimalarial drug target.